DETERMINING INVENTORY POLICIES BY COMPARING PERPETUAL SINGLE ITEM, PERIODIC MULTI-ITEM, AND LEAD TIME REDUCTION MODELS AT PT SINARMAS DISTRIBUSI NUSANTARA - Bintang, Aditya
PT Sinarmas Distribusi Nusantara is a national distribution company engaged in sales and distribution services. One of the company's business partners is PT Unilever, which produces goods in the fields of Nutrition or food and beverages, Personal Care, Home Care or household care, and Beauty & Well-Being or skin care and wellness products. During 2022, PT Sinarmas Distribusi Nusantara experienced an increase in sales quantity. However, this increase was also accompanied by an increase in the number of lost sales, averaging 16% per month during 2022. Based on the root cause analysis using the fishbone diagram, inventory policy proposals need to be determined in order to improve the performance criteria of the company's inventory system. The purpose of this study is to determine inventory policies that can minimize total inventory costs. The proposal determination is carried out for all items that fall into category A. In this study, there are 116 types of Beauty & Well-being items that have the largest contribution with a fund absorption value of 80% and are normally distributed. The models used as a reference for calculating proposed policies include the Q model, P model adjustment for multi-item, and lead time reduction model by Priyan & Uthayakumar (2015). The proposed inventory policy successfully reduced the total costs consisting of ordering costs, holding costs, and shortage costs for all three suppliers. The total cost for 58 types of items that fall into Supplier 1 was successfully reduced from Rp153,109,096 to Rp48,388,744. Then, the total cost for 56 types of items in Supplier 2 was reduced from Rp235,697,593 to Rp58,588,756. Finally, two types of items in Supplier 3 were reduced from Rp4,177,758 to Rp2,498,849. The research results also increased the level of service with an average of 2.94% for Supplier 1, 3.39% for Supplier 2, and 2.27% for Supplier 3. The study also showed that the proposed model is sensitive to changes in demand, ordering costs, and holding costs parameters.